The Effect of Hypertension as a Comorbid Factor on the Length of Stay in Patients Undergoing Cholecystectomy - Albertus Magnus Arya Abisatya; Diah Purwaningsari; Wahyu Prasasti Mutiadesi; Redemptus Yudadi (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: One of the gold standard procedures for cholelithiasis is cholecystectomy. Cholecystectomyhas numerous variated Length of stay results relies upon every nation and medical clinic. Hypertensionis perhaps the most widely recognized comorbid factors and are thought to impact prolonged length ofstay.Aim of Research: To study the effect of hypertension as a comorbid factor on the length of stay in patientsundergoing cholecystectomy in Dr. Ramelan Naval Hospital Surabaya from June 2019-September 2020.Method of Research: This is an analytic descriptive research with retrospective study. The samplingtechnique used in this research is total sampling. The data were collected from medical record data ofpatients at the Internal Medicine and Digestive Surgery Polyclinic.Result of Research: The number of patients who underwent cholecystectomy with hypertensionwho underwent a length of stay > 5 days were 36 people (83.7%). The result from the CoefficientContingency test shows that there is a correlation between hypertension as a comorbid factor and thelength of stay (p<0,0001).Conclusion: This research shows that there is comorbidity such as hypertension affects the length ofstay in cholecystectomy.